TECHNOLOGICAL PROCESS OF OVERSIZED TRANSPORT (Perner's Contacts, 2009)
This article is focused on technology process of oversized transport. Main topic is solution of particular activities duration and schedule making of these activities.
Keywords: activity duration; time reserve; activities schedule